KONSEPSI PELAKSANAAN PENGGABUNGAN PROGRAM SEAAC DENGAN KURIKULUM TARUNA KORPS PELAUT AGAR LEBIH SIAP MENJADI PERWIRA DIVISI NAVIGASI DI KRI - Sachroni Aminnudin; Yoos Suryono Hadi; Agus Makhrow (Saintek: Jurnal Sains Teknologi dan Profesi Akademi Angkatan Laut, 2021)
The learning process is a very significant process in determining the ability levelof the cadets. It is proven that in the research that has been carried out, it has receivedinformation that young officers who have just graduated from the Naval Academy(AAL) in the field show that 54% are not capable and 46% are able to meet the needsaccording to the job description when serving on ships and in battalions. . From thesedata, it can be concluded that adolescent officers are still lacking in mastery of amaterial science. Therefore, there is a need for an evaluation of the learning methodsimplemented in AAL and a review needs to be carried out. In the process of analyzingthe research data carried out, according to the experts and users in the Fleet, it is truethat the mastery of the professional knowledge of the young officers of the MarineCorps when in service is still lacking. Teenage officers are still not fully mastered andare still not quick to make decisions. In this case, the author carried out research usinga qualitative descriptive concept development method, namely the SEAAC (SeamanOfficer Application Course) program, which is a program with a direct practice systemand application to the actual media, namely ships with the aim of increasing the abilityof the cadets of the Marine Corps. and to prepare to become a professional navigationdivision officer. So that by combining the SEAAC program with the Marine Corps CadetEducation Curriculum which will be carried out for 3 months with 3 stages, it will be ableto increase the ability of teenage officers who serve as officers in the navigation divisionon ships. Thus, the SEAAC program will be mapped into the AAL education curriculumwith the hope that in the future it will always be focused and inspiring and creative inthe scope of learning and teaching methods. So that it will create an atmosphere ofinterest between the cadets and the lessons delivered so that the targets set by AALwill be achieved, namely increasing the ability of the cadets of the Marine Corps toprepare themselves to become more professional navigation division officers.